KAJIAN PARTISIPASI MASYARAKAT TERHADAP KEBERSIHAN LINGKUNGAN DI DESA PARA LELLE KECAMATAN TATOARENG KABUPATEN KEPULAUAN SANGIHE - Alamat, Jafar; Andaria, Kalvin Salindeho; Lobja, Xaverius Erick; Vidi Feronika Kapoh; Nismawati (Jurnal Social Science, 2025)
The aim of this research is to examine community participation in environmental cleanliness in Para Lelle Village, Tatoareng District, Sangihe Islands Regency. The research method used in this research is a qualitative descriptive research method, with data collection techniques namely observation, interviews and documentation. The results of this research 1)Forms of community participation in maintaining environmental cleanliness in Para Lelle Village are seen based on the context, namely real forms of participation consisting of labor participation and skills participation. Meanwhile, forms of community participation in maintaining environmental cleanliness in Para Lelle Village are seen based on their involvement, namely direct participation. 2)The level of community participation in maintaining environmental cleanliness in Para Lelle Village is still relatively low and medium. 3)There are two factors that influence community participation in maintaining environmental cleanliness in Para Lelle Village, namely driving factors and inhibiting factors. The driving factors for community participation in maintaining environmental cleanliness in Para Lelle Village are the level of knowledge, length of stay, and the role of government and community leaders. The factors inhibiting community participation in maintaining environmental cleanliness in Para Lelle Village are employment, level of knowledge, the role of government, and facilities and infrastructure.